PTU-056 The effect of hepatitis C infection on the utility of alpha-fetoprotein as a surveillance marker for tumour recurrence following liver transplantation for hepatocellular carcinoma. (28th May 2012) - Maggs, J R L; O'Grady, J G; Heneghan, M A; Agarwal, K; Aluvihare, V; Srinavasan, P; Prachalias, A; Heaton, N; Suddle, A R
Abstract : Introduction: In selected patients, liver transplantation (LT) is considered a curative treatment for hepatocellular carcinoma (HCC). With the application of strict eligibility criteria the risk of tumour recurrence can be minimised but never entirely eliminated. Historically, HCC recurrence is associated with a poor prognosis; however the new and evolving systemic therapies may improve outcomes. Hence, there may be a potential beneficial role for early diagnosis. Although, serum alpha-fetoprotein (AFP) measurement is commonly employed in HCC surveillance in at-risk patients, its role following LT for HCC is not clearly defined. Therefore, we have explored (1) the utility of AFP as a biomarker for tumour recurrence following LT in patients with HCC and (2) the influence of liver disease aetiology on its diagnostic performance. Methods: The clinical characteristics, laboratory parameters and outcomes of 302 patients with HCC who underwent LT between January 1999 and July 2011 at our institution were reviewed. Serum AFP levels following LT were analysed and the area under a receiver-operator characteristic curve (AUC) calculated to assess the performance of AFP as a diagnostic test for HCC recurrence. Results: Recurrent HCC was observed in 13% of patients during the follow-up period. Recurrence was associated with higher pre-LT AFP (98 ng/ml vs 11.5 ng/ml, p>0.001), vascular invasion in the liver explant, and greater tumour size. Following LT, the median time from initial rise in serum AFP to the diagnosis of recurrence was 16 weeks. In our cohort, AFP was an effective predictor of HCC recurrence (AUC 0.843) and using a cut-off value of ≥10 ng/ml was an excellent exclusion test (negative predictive value 0.94). Furthermore, its performance was superior in patients with AFP-secreting tumours at LT, in comparison to those with non-secreting tumours (AUC 0.892 vs 0.710). Patients with chronic hepatitis C (CHC), in comparison to non-infected patients, were younger (56 years vs 60 years, p=0.887) and had a lower MELD score (13 vs 10 ng/ml, p=0.002) but higher serum AFP (21 ng/ml vs 10 ng/ml) at LT. However, there was no difference in recurrence rates between groups. In patients with CHC, AFP was an inferior predictor of HCC recurrence, in comparison non-CHC patients (AUC 0.769 vs 0.887). Conclusion: We, therefore, conclude that serum AFP measurement is a potentially useful surveillance investigation for tumour recurrence post-LT for HCC particularly in patients without CHC. Competing interests: None declared.